Animal-friendly behavioral testing in field studies: examples from ground squirrels - Nunes, Scott (Frontiers in Behavioral Neuroscience, 2023)
Field studies of behavior provide insight into the expression of behavior in its natural ecological context and can serve as an important complement to behavioral studies conducted in the lab under controlled conditions. In addition to naturalistic observations, behavioral testing can be an important component of field studies of behavior. This mini review evaluates a sample of behavioral testing methods in field studies to identify ways in which behavioral testing can be animal-friendly and generate ethologically relevant data. Specific examples, primarily from studies of ground squirrels, are presented to illustrate ways in which principles of animal-friendly behavioral testing can be applied to and guide testing methods. Tests conducted with animals in their natural habitat and that elicit naturally occurring behavioral responses can minimize stress and disturbance for animals, as well as disruption of the larger ecosystem, and can have high ethological validity. When animals are trapped or handled as part of a study, behavioral testing can be incorporated into handling procedures to reduce overall disturbance. When behavior is evaluated in a testing arena, the arena can be designed to resemble natural conditions to increase the ethological relevance of the test. Efforts to minimize time spent in testing arenas can also reduce disturbance to animals. Adapting a behavioral test to a species or habitat conditions can facilitate reduced disruption to subjects and increased ethological relevance of the test.